Selective cobalt nanoparticles for catalytic transfer hydrogenation of N-heteroarenes. Issue 9 (12th July 2017) - Chen, Feng; Sahoo, Basudev; Kreyenschulte, Carsten; Lund, Henrik; Zeng, Min; He, Lin; Junge, Kathrin; Beller, Matthias
Abstract : Nitrogen modified cobalt nanoparticles are easily prepared from melamine or melamine resins. The resulting catalysts show excellent selectivity for transfer hydrogenation of N-heteroarenes. Abstract : Nitrogen modified cobalt catalysts supported on carbon were prepared by pyrolysis of the mixture generated from cobalt(ii ) acetate in aqueous solution of melamine or waste melamine resins, which are widely used as industrial polymers. The obtained nanostructured materials catalyze the transfer hydrogenation of N-heteroarenes with formic acid in the absence of base. The optimal Co/Melamine-2@C-700 catalyst exhibits high activity and selectivity for the dehydrogenation of formic acid into molecular hydrogen and carbon dioxide and allows for the reduction of diverse N-heteroarenes including substrates featuring sensitive functional groups.